THE ROLE OF CORRECTIONAL GUARDIANS IN PERSONALITY DEVELOPMENT TO IMPROVE PRISONERS' SELF-CONTROL AT CLASS IIA CURUP CORRECTIONAL FACILITY - Jehan Aidil Ruwanda; Markus Marselinus Soge (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the role of correctional counselors (Wali Pemasyarakatan) in enhancing inmates’ self-control through personality development programs at the Class IIA Curup Correctional Facility. Correctional counselors act as facilitators, communicators, and motivators in supporting inmate rehabilitation and social reintegration. Strengthening self-control is considered essential to prevent recidivism and help inmates adapt successfully to life after release. The findings show that counselors play an active role in conducting risk assessments, assisting inmates in the reintegration process, and supervising spiritual and personality development programs. They also maintain ongoing communication with inmates and provide emotional support, which contributes to improving inmates’ self-awareness and behavioral control. However, several challenges hinder the effectiveness of their role, including limited facilities, an imbalance between the number of officers and inmates, diverse inmate backgrounds, and the lack of specialized psychological training for counselors. Therefore, it is necessary to improve infrastructure, increase the number of correctional staff, and provide targeted training programs to strengthen counselors’ competencies. These efforts are expected to enhance the effectiveness of personality development programs and support successful inmate reintegration into society. Keywords: Correctional Counselor; Personality Development; Self-Control; Inmates